Multi-Sensor Information Fusion - Gao, Yuan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book includes papers from the section "Multisensor Information Fusion", from Sensors between 2018 to 2019. It focuses on the latest research results of current multi-sensor fusion technologies and represents the latest research trends, including traditional information fusion technologies, estimation and filtering, and the latest research, artificial intelligence involving deep learning.